The Association Between Left Ventricular Hypertrophy and the Occurrence and Prognosis of Atrial Fibrillation: A Meta-Analysis - Xiang, Huaqiang; Xue, Yangjing; Chen, Zhi; Yu, Yongwei; Peng, Yangpei; Wang, Jinsheng; Ji, Kangting; Zhu, Huifen (Frontiers in Cardiovascular Medicine, 2021)
Aims To perform a meta-analysis of studies of the association of left ventricular hypertrophy (LVH) and atrial fibrillation (AF), especially the predictive and prognostic role of LVH. Methods and results We searched Medline, Embase, and the Cochrane Library from inception through 10 April 2020. A total of 16 cohorts (133,091 individuals) were included. Compared with normal subjects, patients with LVH were more susceptible to AF (RR = 1.46, 95% CI, 1.32–1.60). In patients with AF and LVH, there was a higher risk of all-cause mortality during 3.95 years (RR = 1.60, 95% CI, 1.42–1.79) and these patients were more likely to progress to persistent or paroxysmal AF (RR = 1.45, 95% CI, 1.20–1.76) than were patients without LVH. After catheter ablation of AF, patients with LVH were more likely to recur (RR=1.58, 95% CI, 1.27–1.95). Conclusion: LVH is strongly associated with AF and has a negative impact on outcome in patients with AF.